Probing the Structures of Viral RNA Regulatory Elements with SHAPE and Related Methodologies - Rausch, Jason W.; Sztuba-Solinska, Joanna; Le Grice, Stuart F. J. (Frontiers in Microbiology, 2018)
Viral RNAs were selected by evolution to possess maximum functionality in a minimal sequence. Depending on the classification of the virus and the type of RNA in question, viral RNAs must alternately be replicated, spliced, transcribed, transported from the nucleus into the cytoplasm, translated and/or packaged into nascent virions, and in most cases, provide the sequence and structural determinants to facilitate these processes. One consequence of this compact multifunctionality is that viral RNA structures can be exquisitely complex, often involving intermolecular interactions with RNA or protein, intramolecular interactions between sequence segments separated by several thousands of nucleotides, or specialized motifs such as pseudoknots or kissing loops. The fluidity of viral RNA structure can also present a challenge when attempting to characterize it, as genomic RNAs especially are likely to sample numerous conformations at various stages of the virus life cycle. Here we review advances in chemoenzymatic structure probing that have made it possible to address such challenges with respect to cis-acting elements, full-length viral genomes and long non-coding RNAs that play a major role in regulating viral gene expression.